P-214 A Study of Fecal Microbiota Transplantation in Pediatric Patients with Inflammatory Bowel Disease. (March 2016) - Goyal, Alka; Kufen, Adam; Jackson, Zachary; Morowitz, Michael
Abstract : Background: Inflammatory bowel disease (IBD) is chronic immune-mediated process associated with alterations in gut microbial composition and function. Fecal microbiota transplantation (FMT) has been a breakthrough in treatment of recurrent clostridium difficile infection (CDI). While the early studies on FMT in IBD are encouraging, the data is still sparse and results have been more variable than with recurrent CDI. In this report, we describe clinical findings on the first 12 subjects from an ongoing clinical trial of FMT in pediatric IBD patients (ClinicalTrials.gov NCT02108821). Methods: Patients with IBD who were flaring on standard medical therapy who but were C. difficile negative were eligible. The fecal donors were healthy family members with normal bowel function and negative infectious disease testing. FMT was done by duodenoscopy/jejunoscopy, and colonoscopy routes. Disease activity was assessed using fecal calprotectin, and PCDAI (Pediatric Crohn's Disease Activity Index) or PUCAI (Pediatric Ulcerative Colitis Activity Index) scores. Results: Median age at diagnosis was 8.7 years (4.6–17 years). Median age at FMT was 11.4 years (8.3–21.2 years); time interval between initial diagnosis to FMT was 2.6 years (0.7–6.7 years). The initial diagnosis was UC in 9 patients and CD in the other 3. Out of 12 subjects enrolled, 7 cases of UC and 2 of CD have completed 6 months follow-up. All patients tolerated FMT well (n = 12). Side effects were mild and managed symptomatically. These included abdominal discomfort (n = 7), diarrhea (n = 3), bloating (n = 2) and emesis (n = 3). One patient had a low-grade fever. One patient developed fever and diarrhea due to persistent UC disease activity. At baseline, PUCAI score ranged between 12.5 and 32.5 (n = 9), while PCDAI scores ranged between 12.5 and 32.5 (n = 2); one patient with CD was clinically asymptomatic but had active disease based on histology and elevated calprotectin levels. At one week post-FMT, 6 out of 9 UC cases had a reduction in PUCAI score of >15 from baseline. At one month post-FMT, 7 out of 8 evaluable UC cases had a reduction in PUCAI score of >15 from baseline. At 6 month post-FMT, 3 out of 7 evaluable UC cases had a reduction in PUCAI score of >15 from baseline. Out of 7 UC patients with 6 months follow-up, 4 had short-lived clinical improvement lasting 2 weeks to 5 months, 2 did not respond while one remains in clinical remission. Of the 2 CD patients with 6 months follow-up, one did not respond while the other one remains in clinical remission. Fecal calprotectin was elevated in 9 out of 10 patients pre-FMT (range 84 to >2000 μg/g; ULN 162). Following FMT, fecal calprotectin appeared to track clinical disease activity, with normal values in both patients who remain in remission. Conclusions: In this preliminary report, FMT was safe and well tolerated in pediatric patients with IBD flare not related to C. difficile infection. We observed significant clinical responses in over 50% patients but the symptomatic benefit was short-lived. Deep sequencing on mucosal biopsies and microbiome studies on recipient-donor fecal samples will be performed for correlative analyses.